The Design and Evaluation of Emergency Call Taking User Interfaces for Next Generation 9-1-1 - Dash, Punyashlok; Neustaedter, Carman; Jones, Brennan; Yip, Carolyn (Frontiers in Human Dynamics, 2022)
In the coming years, emergency calling services in North America will begin to incorporate new modalities for reporting emergencies, including video-based calling and picture sharing. The challenge is that we know little of how future call-taking systems should be designed to support emergency calls with rich multimedia and what benefits or challenges they might bring. We have conducted three studies, along with design work, as part of our research to address this problem. First, we conducted observations and contextual interviews within three emergency response call centres to investigate call taking practices and reactions to the incorporation of rich multimedia in emergency call taking practices. Following this, we created user interface design mock-ups and conducted two additional studies with call takers. One involved low-fidelity designs and one involved the use of a medium-fidelity digital prototype. Across the studies, our results show that 9-1-1 call takers will need a next generation interface that supports multimedia, including video calling, as part of calls. Yet user interfaces will need to be different from commercial video conferencing applications that are commonplace today. Design features for 9-1-1 systems must focus on supporting camera work and the capture of emergency scenes; situational awareness of incidents across call takers, including current and historical media associated with them; and, the regulation of media flow to balance privacy concerns and the viewing of potentially traumatic visuals.